PENGARUH KONTRIBUSI DANA DESA TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA LOLEBA - Nova Liska Lanty; Anhar Drakel; Faisal Y Habsyi (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2023)
The type of research used in this study is quantitative research with the aim of measuring the effect of village fund contributions (X1) on the welfare of the Loleba village community (Y). The analytical tool used in this study is simple regression. The results of the study indicate that village fund contributions have an effect on the welfare of the Loleba village community, South Wasilei sub-district, East Halmahera district.